Hemoglobin levels and red blood cell indices in mid-gestational fetuses with beta-thalassemia/HbE, beta-thalassemia trait or Hb E trait and normal fetuses - Srisupundit K. (2014)
Objective: To compare red blood cell indices among normal, beta-thalassemia trait or hemoglobin (Hb) E trait, and beta-thalassemia/Hb E diseases mid-gestational fetuses. Methods: One hundred seventy-five fetuses at risk of beta-thalassemia/Hb E disease undergoing cordocentesis with determination of Hb levels and red blood cell indices at mid-pregnancy were recruited. The fetal diagnoses were based on fetal Hb typing and DNA analysis. The fetuses were divided into three groups: normal, beta-thalassemia trait or Hb E trait, and beta-thalassemia/Hb E disease. Results: The prevalence of beta-thalassemia/Hb E disease, beta-thalassemia trait or Hb E trait, and normal fetuses was 32.6% (57 cases), 28.6% (50 cases) and 36.6% (64 cases), respectively. Mean Hb levels and red blood cell indices were not significantly different among the three groups of fetuses. However, almost 10% of beta-thalassemia/Hb E fetuses had some degree of anemia. The most anemic fetuses had a β0 mutation. Conclusion: There is no significant difference in Hb level and red blood cell indices among fetuses at risk of beta-thalassemia/Hb E disease. © 2013 John Wiley & Sons, Ltd.